EFEKTIFITAS PEMBERIAN BAHAN BIOGEOTEKSTIL TERHADAP KERAGAMAN MIKORIZA SEBAGAI UPAYA PENINGKATAN PRODUKSI TANAMAN KENTANG DI ANDISOL, BATU - Muhammad Iqbal Boechori; Didik Suprayogo (Jurnal Tanah dan Sumberdaya Lahan, 2018)
Mycorrhiza is a symbiotic fungus with plant roots that is useful for transferring nutrients to plant roots. Potato (Solanum tuberosum L.) is a good host for mycorrhizal growth. Intensive cultivation of potatoes can result in land degradation due to land clearing that does not follow conservation rules, which may lead to a decrease in productivity of potato. This study focused on management of cultivation by occurrence erosion affecting potato cultivation system, and its effect on diversity of mycorrhiza for potato production in an Andisol of Batu. This study usea a completely randomized design factorial with 2 factors: (1) geotextile (2) organic mulch, obtained 24 treatment combinations and 3 replications. Organic mulch doses administered at each treatment were equivalent to 10 t ha-1. The results showed that biogeotextile application had a significant effect on population diversity of mycorrhiza that increased diversity and root infection 10% more compared without application that had no significant effect. The existence of biogeotextile affected soil chemical properties in the form of soil organic matter that increased 2-fold compared with no application. Biogeotextile could increase tuber diameter by 43%, number of tubers by 67%, and potato tuber weight 2 times than without application. The treatment of elephant grass gave the best influence on potato production.